Fatigue life evaluation of composite material sleeve using a residual stiffness model. (August 2017) - Kim, Jong-Sung; Bae, Kyung-Dong; Lee, Chul; Kim, Yun-Jae; Kim, Woo-Sik; Kim, Ik-Joong
Highlights: Fatigue life assessment is performed for the buried natural gas pipe repaired using a composite material sleeve. Lap shear tensile and fatigue tests are performed to determine mechanical properties and a cohesive damage model. It is found that damage of the adhesive does not significantly affect the fatigue lifetime of the buried natural gas pipe. Abstract: In this study, fatigue assessment was performed to evaluate fatigue lifetime of the buried natural gas pipe repaired using a composite material sleeve. Lap shear tensile and shear fatigue tests were firstly carried out in order to determine mechanical properties and to establish a damage model. Then from the test results, the damage model of the composite material sleeve was determined, based on stiffness reduction phenomenon due to adhesive damage. Via finite element damage analysis using the damage model and a structural stress/fracture mechanics approach presented in ASME B&PV Code Sec. VIII Div. 2, delamination behavior, burst pressure of the damaged pipe and fatigue lifetime of the damaged pipe after occurrence of the delamination are investigated. As results, it is confirmed that damage of the adhesive did not significantly affect the fatigue lifetime of the buried natural gas pipe even when delamination between composite layers due to adhesive damage occurred around corroded damage of the pipe.